Selecting the Safety and Cost Optimized Geo-Stabilization Technique for Soft Clay Slopes - Kennedy C. Onyelowe; Ahmed M. Ebid; Hisham A. Mahdi; Jair A. Baldovino (Salehan Institute of Higher Education, 2023)
Slope failure poses a serious threat to the built environment as it is currently one of the fundamental contributors to climate change fears across the world, and this threatens the environmental goals of the United Nations Sustainable Development Goals (UNSDGs) for the year 2050. In this research paper, an optimized geo-stabilization numerical model has been developed with a Plaxis 2D code under safety and cost optimization considerations for a 37 m high slope embankment located on a soft clay watershed with an infinite extension. The site was prepared with four monitoring wells installed at 2.5 m, 7.5 m, 12.5 m, and 21.5 m from the foot of the slope to measure the water level conditions, and samples were collected and tested in the laboratory to determine the hydraulic and shear strength and modulus of the soil. Seven (7) different simulation alternatives were considered in terms of the model solutions to be deployed under dry and wet states, which were slope steep (angle) reduction (Alt-1), dewatering (Alt-2), jet grouting (Alt-3), jet grouting/dewatering (Alt-4), slope reduction/jet grouting (Alt-5), slope reduction/dewatering (Alt-6), and slope reduction/jet grouting/dewatering (Alt-7). The finite element model implementation of the alternatives showed that Alt-2, Alt-3, and Alt-4 had FOS of less than 1.5 and were omitted because their stability considerations did not meet the requirements for the normal operating conditions of a slope and also the short-term and long-term stability conditions according to the literature. Alternatives 1, 5, 6, and 7 with FOS above 1.5 were selected for further optimization considerations. Economic and sustainability factors were selected and considered based on the cost in line with current average market prices, constructability, reliability, and the environmental impact needed to achieve the required earthwork, jet grouting, dewatering, and selected combinations. Finally, the Alt-1 (FOS = 1.505), though not the cheapest, was selected as the optimal choice in terms of reliability, constructability, and environmental impact. However, Alt-6 (FOS = 1.520) and Alt-7 (FOS = 1.508) are the most economical but ranked low in reliability and environmental impact considerations. Doi: 10.28991/CEJ-2023-09-02-015 Full Text: PDF